MENDAPAT BAYARAN DIBAWAH KETENTUAN UPAH MINIMUM REGIONAL (UMR) - Kirti, Harin Nadindra (Notarius, 2018)
AbstractRemuneration is the most vulnerable and the most important in the relationship between labor and employers also have differences and even frequent conflicts, especially if it is associated with the perception or interpretation that is not the same on the interests of each party that basically does have differences, so that study of the legal protection of the labor mendapatk paid below the regional minimum wage needs to be analyzed properly in order to achieve the welfare of workers. Issues examined in this research is how the legal protection for workers who are not in wages in accordance with the provisions of the minimum wage cities / districts in the city, as well as how the dispute resolution to resume the work force of less than 10 people, who do not earn the minimum wage. The method used in this research is the empirical juridical approach. The results of this study finally provides an answer that the legal protection for workers who are not in wages in accordance with the provisions of the minimum wage city / county in the city of Semarang is to make a complaint to the All Indonesian Workers Union (SPSI) Semarang to be pursued advocacy and admonition to the employer the conflict in order to realize the protection and welfare of workers, related to the settlement of disputes to the CV workforce of less than 10 people who do not get the minimum wage is that it can be done by utilizing a system of Pancasila Industrial Relations with the aim to advise the order to resolve the issue amicably and consensus by Entrepreneur with workers so that outcomes could satisfy both sides.   AbstrakPengupahan merupakan bagian yang paling rawan dan paling penting di dalam hubungan antara tenaga kerja dan pengusaha yang sering kali menimbulkan konflik. Hal ini membuat kajian tentang perlindungan hukum terhadap tenaga kerja yang  dibayar dibawah ketentuan upah minimum regional perlu dianalisis dengan baik, demi terwujudnya kesejahteraan bagi tenaga kerja. Masalah dalam  penelitian ini adalah bagaimanakah perlindungan hukum terhadap tenaga kerja yang tidak di upah sesuai dengan ketentuan upah minimum kota/kabupaten di Kota Semarang, serta bagaimana penyelesaian sengketa terhadap CV yang tenaga kerjanya kurang dari 10 orang, yang tidak mendapatkan upah sesuai UMR. Metode yang digunakan dalam penelitian ini adalah dengan pendekatan yuridis empiris. Hasil penelitian ini menunjukkan bahwa perlindungan hukum terhadap tenaga kerja yang dibayar di bawah ketentuan upah minimum kota/kabupaten di Kota Semarang adalah dengan melakukan pengaduan kepada Serikat Pekerja Seluruh Indonesia (SPSI) Kota Semarang untuk diupayakan advokasi hingga peneguran kepada pihak pengusaha yang terlibat konflik, terkait penyelesaian sengketa terhadap CV yang tenaga kerjanya kurang dari 10 orang yang tidak mendapatkan upah sesuai UMR adalah dengan memanfaatkan Sistem Hubungan Industrial Pancasila dengan tujuan untuk menyarankan kepada para pihak, baik pengusaha maupun tenaga kerja, agar menyelesaikan persoalan secara musyawarah dan mufakat sehingga hasil yang dicapai dapat memuaskan kedua belah pihak.